(untitled) (Journal of Parents and Teachers, 2025)
The article analyzes what children learn at each stage; more specifically, it focuses on God and how to convey His image to children. It also presents the idea that for a believer, it is very important to pass on this legacy to their children, helping them understand that God is both our father and our mother.